Ablation of residual Barrett's epithelium after endoscopic resection: A randomized long-term follow-up study of argon plasma coagulation vssurveillance (APE study) - Manner, Hendrik; Rabenstein, Thomas; Pech, Oliver; Braun, Kirsten; May, Andrea; Pohl, Juergen; Behrens, Angelika; Vieth, Michael; Ell, Christian (Endoscopy, 2014)
Background and study aim: It is commonly assumed that ablation of any remaining Barrett's epithelium after endoscopic resection of early Barrett's neoplasia improves outcome by reducing the rate of metachronous lesions, but this has not yet been evaluated in a randomized trial. The aim of this study was to compare argon plasma coagulation (APC) with surveillance only for the management of residual Barrett's epithelium following endoscopic resection. Patients and methods: Patients in whom focal early Barrett's neoplasia (high grade intraepithelial neoplasia [HGIN] or mucosal cancer) had been curatively resected by endoscopy were randomly assigned to undergo ablation of the residual Barrett's segment by APC or surveillance only; pH-metry-adjusted proton pump inhibitor therapy was administered in both groups. The main outcome parameter was recurrence-free survival. Follow-up endoscopies with biopsies in cases of further residual Barrett's epithelium were carried out at 6-monthly intervals in both groups. Results: A total of 63 patients (57 male [90.5%]) were included in the study (ablation group n=33; surveillance group n=30). For complete Barrett's ablation, a mean number of 4±1.6 APC sessions were required (range 2-7). The mean follow-up duration did not differ significantly between ablation (28.2±13.7 months, range 0-44) and surveillance patients (24.7±14.8 months, range 0-45; P=0.159). The number of secondary lesions was 1 in the ablation group (3%), and 11 in the surveillance group (36.7%), leading to significantly higher recurrence-free survival for the patients undergoing ablation (P=0.005). Conclusions: Thermal ablation of residual Barrett's epithelium leads to a significant reduction in neoplasia recurrence rate compared with a surveillance strategy during a limited follow-up of 2 years. A longer follow-up duration may have led to a relatively higher rate of secondary neoplasia in both groups of patients.©Georg Thieme Verlag KG Stuttgart.
CRIS-Team Scopus Importer:2025-03-05